Identifying Brand Influencer and FOMO Marketing: Strategies Through Smart Buying Decision to Counter Impulsive Buying of Skincare Products - Mery Lani Purba; Elisabeth Tambunan; Marupa Siregar; Dian Angelia Pasaribu; Eben Ezer Sopater Saragih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The skincare industry has experienced rapid growth, with an increasing number of consumers becoming more concerned about their skin health and beauty. This study examines the impact of influenced brand marketing strategies and the fear of missing out (FoMO) on impulsive purchases of skincare products, considering the mediating role of smart purchasing decisions. The uniqueness of this study lies in testing the interaction between psychological factors, such as FoMO with the influence of influencers as well as the level of consumer rationality in the ever-evolving beauty market. Using an explanatory quantitative research design, data were collected through questionnaires from 216 millennial and Gen Z consumers in Medan. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that brand influencers have a positive and significant effect on smart purchasing decisions, but do not have a direct effect on impulsive purchasing. Conversely, FoMO proved to be a very strong and significant driver of impulsive buying, while also negatively affecting consumers’ ability to make smart purchasing decisions. It was found that smart purchasing decisions did not act as a mediator in the relationship between brand influence and impulsive buying.